Effect of Raphia vinifera Fibre Size and Reinforcement Ratio on the Physical and Mechanical Properties of an Epoxy Matrix Composite: Micromechanical Modelling and Weibull Analysis - Syrille Brice Tchinwoussi Youbi; Omar Harzallah; Nicodème Rodrigue Sikame Tagne; Paul William Mejouyo Huisken; Tido Tiwa Stanislas; Jean-Yves Drean; Sophie Bistac; Ebenezer Njeugna (International Journal of Polymer Science)
This study evaluates the effects of lengths and reinforcement ratio of Raphia vinifera fibres (RVFs) on the physical and mechanical properties of an epoxy matrix composite. Three volume fractions (20%, 30%, and 40%) and three lengths (5, 10, and 15 mm) of fibres were used to produce the composite, and the samples were subjected to the absolute and apparent density, porosity, water absorption rate, and tensile and flexural strength. The probability of failure of the composite is described by the means of two-factor Weibull model. In addition, a theoretical approach to predict mechanical characteristics based on empirical models was carried out. The results show that the addition of RVF decreases the density of the composite, while the porosity and absorption rate increase. The mechanical test shows that the tensile and flexural stress and Young’s modulus of the composite are lowered compared to those of the resin alone. Multivariate analysis of variance (MANOVA) and Tukey test showed that fibre lengths and reinforcement ratio significantly lower the mechanical properties of the composite. The distribution of strength and Young’s modulus follows Weibull’s law. Furthermore, the Cox–Krenkel mathematical model has the best approximated model for the experimental results after the tensile test. Based on these results, this material could be used as reinforcement parts for vehicle backrests or interior decoration in the construction industry.